Space travel in a high altitude environment: Biology by-passing the pressure laws of physics and BioSpaceFormin g - Zubieta-Calleja, Gustavo Rafael; Zubieta-DeUrioste, Natalia (Revista Cubana de Investigaciones Biomédicas, 2019)
After the accident on Apolo1, with 100% oxygen in the cabin, all spaceships now travel with a sea level pressure and 20.9% oxygen. Extravehicular activity requires lowering the pressures. It is complex and time consuming. Permanently reducing the cabin pressure would be a great advantage. A paper by NASA in 2013, proposed for the spaceflight environment: 8 psia / 32% O2 (reducing the sea level pressure (14.7 psi / 20.9% O 2), but increasing the fraction of oxygen in order to replicate the sea level PaO2). However, we question this proposal, as it is based on the fear of hypoxia. Our proposal back in 2007 suggested that space travel should take place in a hypobaric environment of 9.5 psi / 20.9% O2 (like in the city of La Paz-Bolivia (3,600m) [11,811ft]). The logic behind it is that at all altitudes on planet Earth, life thrives in a 20.9% Oxygen, 79% Nitrogen. PaCO2 also needs to be considered. In a physiological manner, over 200 million inhabitants of high altitude above 2,000m [6,561ft], have perfectly normal lives. The astronauts could benefit of a Extra-Vehicular Activity (EVA) suit pressure of only 149 mmHg [2.8psi] (lighter, much more comfortable and efficient spacesuits) and space travel anemia could be reduced. The preparation prior-to-space travel could be carried out by adapting and living in a high altitude environment. We consider chronic hypoxia a fundamental step in BioSpaceForming (Adaptation to life in space). As all living beings start to move out of Earth into space, they will have to change their biology and adapt to new conditions.